Optimizing the technique of laparoscopic splenectomy in children - Józef Dzielicki; Andrzej Grabowski; Wojciech Korlacki (Videosurgery and Other Miniinvasive Techniques)
Introduction: The first laparoscopic splenectomy in children was managed in 1993 by Tulman. During the past 15 years,laparoscopic splenectomy has become a gold standard in many centres.Aim: To establish an optimal surgical technique of laparoscopic splenectomy according to our own experience andconcerning clinical and economic aspects.Material and methods: In 1996-2007, 77 laparoscopic splenectomies were carried out in our department. Most of theindications were haematological diseases. Three groups were created from the study population according to theinstruments used for preparation and closure of the vessels. Attention was paid to duration of the procedure, complications,conversions, volume of postoperative blood loss, time of analgesic therapy and length of hospital stay.Results: Mean duration of the procedure was 112 ±53.11 min. Complication rate was 12.98%. There were no statisticallysignificant differences among the three studied groups concerning the number and character of complications.Costs were significantly different in all three groups.Conclusions:1. There are no statistically significant differences in the clinical aspects of perioperative course among the three studiedgroups.2. The use of disposable instruments and especially LigaSure high energy coagulation essentially lowers overall costsof the procedure.